HC-05 PROTOCOL IOT BASED FOR SMART WEARABLE HEART-RATE MONITORING SYSTEM WITH BLYNK APPLICATION - Azwati Azmin; Aiza Mahyuni; Zafirah Faiza; Najwa Rawaida Ahmad; Rabiatul Adawiyah Akhbar; Wan Mohd Yusof Rahiman (Journal of Islamic, Social, Economics and Development, 2022)
Incorporating technology in emergency healthcare would tremendously help tofurther enhance the quality of patient’s care. The application of Internet of Things or IoT intoemergency healthcare could be the better digital solutions to saving lives in the time of rush.The patient’s vital signs, TRIAGE tags and conditions could be updated to the doctors in theemergency department without lag. Both parties can also communicate with one another todiscuss the patient’s treatment. This welcomes more possibilities in telemedicine and disastermanagement. Patients who suffered from serious illness issues such as heart attack, otherrespiratory failures and sudden rise in body temperature need at least IoT based wearablehealth monitoring systems for continuous physiological data monitoring in real-time basis. Thiswearable health monitoring systems can provide better transformation information compare tothe general health issues for each individuals. The implementation of IoT based wirelesstechnologies in this project create a new alternative way in the medical stuff to convert theconventional health care system, by replacing the current practice to a wearable monitoringvital sign systems, which is more efficient. The objective for this research is to develop awearable device capable of monitoring and transmitting vital signal patients in real-time basisand to create low-cost, greater mobility for a doctor to provide consultation to the patient inprompt action. In specific, wireless devices and techniques for monitoring heart, pulse rate andtemperature are discussed.